Simulation of liquefaction-induced damage of the Port of Long Beach California Using the UBC3D-PLM model (2016)
This research is presented to develop the following specific objectives: i) to calibrate constitutive model parameters after a compilation of published subsurface investigation reports of the POLB and to determine the suitability of these parameters to reproduce laboratory tests following different stress paths and shear strain levels; ii) to assess the use of advanced constitutive models like the UBC3D-PLM to predict the behavior of the POLB when a seismic event induces liquefaction; iii) to provide recommendations related to the resulting permanent deformations and residual strength of soils which could compromise the resiliency of the port. To achieve these goals, was used a numerical analyses using the UBC3D-PLM soil model to determine the onset of liquefaction and estimate ground-induced settlements based on post-liquefaction excess pore water pressure dissipation. This work presents the results of boundary value element simulations of cyclic direct simple shear, monotonic triaxial compression, numerical simulations of the free-field response and of different story structures in the site when an Operating and Contingency Levels Earthquake occur. In general, it has been observed that the model has certain limitations but is capable to predict the onset of liquefaction and the liquefaction-induced settlements after the dissipation of the excess pore water pressure.